A retrospective serological survey on human babesiosis in Belgium. (January 2015) - Lempereur, L.; Shiels, B.; Heyman, P.; Moreau, E.; Saegerman, C.; Losson, B.; Malandrin, L.
Abstract: In Europe, most clinical babesiosis cases in humans have been attributed to Babesia divergens and Babesia sp. EU1. Babesia microti infection of humans occurs mainly in the United States; although a case of autochthonous B . microti infection and serological evidence of infection have been reported in Europe. The Indirect Fluorescent Antibody Test was used to screen sera from 199 anonymous Belgian patients with history of tick bite and clinical symptoms compatible with a tick-borne disease. The serological screen detected positive reactivity in 9% ( n = 18), 33.2% ( n = 66), and 39.7% ( n = 79) of the samples against B . microti, B . divergens, and Babesia sp. EU1, respectively. Thus, evidence of contact among three potentially zoonotic species of Babesia and humans has been confirmed in Belgium. Preventive action and development of better diagnostic tools should help in prevention of clinical cases and to clarify the true burden of such infection for individuals and public health.